Lifetime cost of meningococcal disease in France: Scenarios of severe meningitis and septicemia with purpura fulminans - Stève Bénard; Claire Wright; Jimmy Voisine; Catherine W. Olivier; Joël Gaudelus (Elsevier, 2016)
Summary: Invasive meningococcal disease (IMD) is life-threatening and can result in severe sequelae. In France, no data have been published on the costs of severe IMD cases. Two realistic scenarios were developed with national experts (clinicians and social workers): a 6-year-old child with purpura fulminans with amputation of both legs below the knee (case A) and a 3-year-old with meningitis and severe neurological sequelae (case B). Additional scenarios included other typical sequelae of IMD such as chronic kidney disease (CKD), profound deafness and epilepsy. Data on healthcare, disability, educational and other resource use were obtained from experts and families of patients with similar sequelae. Unit costs (2013) were mainly obtained from the literature and the National Health Insurance (NHI). Time horizon was based on life expectancies of patients (77 and 55 years, respectively). A 4% discount rate decreasing to 2% after 30 years was applied. Costs are presented from the perspective of the NHI, publicly funded organizations and patients' families or their private health insurances. purpura fulminans with amputations is associated with a lifelong discounted cost of €768,875. Adding CKD doubles the amount (€1,480,545). Meningitis with severe neuro-cognitive sequelae results in a lifelong discounted cost of €1,924,475. Adding profound deafness and epilepsy slightly increases the total cost (€2,267,251). The first year is the most expensive in both scenarios (€166,890 and €160,647 respectively). The main cost drivers for each scenario are prostheses and child/adult stays in healthcare facilities, respectively. Overall, patients' families or his private insurance had to pay around 13% of total cost (101,833€ and 258,817€, respectively). This study fills a gap in the body of knowledge on IMD sequelae care and lifetime costs in France. The potentially high economic burden of IMD, in addition to its physical, psychological and social burden, reinforces the need for prevention. Keywords: Invasive meningococcal disease, Management, Cost, Prevention, France